Short landing performance and scale effect of a flapping wing aircraft - Chen, Si; Guo, Shijun; Li, Hao; Tong, Mingbo; Ji, Bing (American Society of Civil Engineers (ASCE), 2020)
An investigation was made into the performance and scale effect of birdlike flapping wing aircraft in short landing. A flapping mechanism is proposed to transform a powered shaft rotation to an optimal kinematics of wing motion combining up-and-down stroke, pitching, and fore-and-back swing. An unsteady aerodynamic method (UAM) was developed based on potential flow theory, including the leading- and trailing-edge vortices generated by a flapping wing. After validation based on computational fluid dynamics (CFD) results, the method is used to calculate the aerodynamic forces of flapping wings. The flight dynamics model of the aircraft is built using Automated Dynamic Analysis of Mechanical Systems (ADAMS) software version 2012 interfacing with the UAM coded in Python. The coupling between the inertial force of the body motion and the aerodynamic forces from flapping wings and tailplane is incorporated into the numerical simulation of the aircraft landing. Taking a 0.196-kg birdlike aircraft model with a prescribed kinematics of flapping wing motion as an example, a parametric study was carried out in a small range of initial tailplane angles and subsequent flapping frequencies. Optimal parameters were obtained to reduce the forward and descending velocities of the aircraft to a minimum value for safe and short landing performance. The study is then extended to aircraft of different geometric scales in a range of 0.5–10 associated with a weight scale of 0.1–1,000. Based on the study, a method is developed to determine the required flapping frequency for birdlike aircraft of different scales to achieve a short landing target with the descending velocity reduced to a specified value. For the aforementioned example aircraft (geometric scale of 1), the flapping frequency is 4 Hz to reduce both descending and forward velocities to 50% of the landing performance in fixed-wing mode, while a birdlike aircraft on a geometric scale of 10 and landing weight of 196 kg requires a minimum flapping frequency of 1.25 Hz to achieve a 50% reduction of the descending and forward velocities compared with the same aircraft landing in fixed-wing mode.